RELEVANCE AND ORIGINALITY OF INTERACTIVE METHODS IN PRESCHOOL EDUCATION - Babanazarova Guzalkhon Odil kizi (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, several interactive methods are given and explained in order to bring innovation to the educational system. The use of interactive methods in education ensures high efficiency. Interactive methods encourage cooperative learning while creating a little competition.